Hubungan Karakteristik Petani Dengan Persepsi Penerapan K3 Pada Petani di Kecamatan Kotamobagu Utara - Hairil Akbar; Krisdayanti Goni; Sarman Sarman; Christien Gloria Tutu; Ni Wayan Dimkatni; Abdul Malik Darmin Asri (Afiasi : Jurnal Kesehatan Masyarakat, 2024)
Farming is one informal sector work and is often indicated dangerous since it involves chemicals as well as tools/machines, which can lead to workplace accidents. The implementation of OSH in the informal sector cannot be applied if there is a lack of knowledge, poor work attitudes and behavior, and the provision of personal protective equipment that the business managers have not fulfilled. There are 37.19% of farmers have experienced workplace injuries in North Sulawesi Based on field observation, the farmers in North Kotamobagu District are still unfamiliar with OSH applications in the workplace. This present work aimed to identify theRelationship Between Farmer Characteristics and Perceptions of The Application of OSH Farmers in the North Kotamobagu District. This quantitative research applied an analytical observational method with cross-sectional study design. The study’s sample consists of 93 participants using simple random sampling.The data collection technique comprised primary data by direct interviews with the farmers, and secondary data obtained from Department of Farming Fishery of Kotamobagy City. Data analysis using univariate, bivariate, and multivariate analysis, in which the bivariate and multivariate employed chi-square and double logistic regression test. Findings It discovered that there are 5 (five) variable candidates to be carried out with double regression, namely: education (p-value =0.018), training (p-value =0.059), land status (p-value =0.000), land area (p-value = 0.000) and knowledge (p-value = 0.000). While the other 3 (three) variables are not included in the candidate variables, namely age (p value =0.101), length of farming (p-value =0.299), and income (p-value =0.207). The final results of multiple regression analysis obtained 2 variables: education and knowledge. The predictive index of perceived OSH implementation was obtained (-1.670 + 1.169* education + 2.149* knowledge).